(untitled) (Indonesian Journal of Agrarian Law, 2026)
Land inequality in Indonesia remains a persistent structural issue, even as the government strengthens its policy on the control and utilization of abandoned land through Government Regulation No. 48 of 2025. This regulation authorizes the use of State Reserve Land (Tanah Cadangan Umum Negara/TCUN) for various purposes, including agrarian reform and national strategic projects, yet it does not establish a clear order of priority. The absence of such prioritization raises concerns about the direction of national agrarian policy and its consistency with the objective of equitable land distribution. This study examines the regulation of abandoned land utilization under Government Regulation No. 48 of 2025 from the perspective of legal certainty and evaluates its implications for the implementation of agrarian reform as mandated by Presidential Regulation No. 62 of 2023. Employing a normative juridical method, the research applies statutory, conceptual, and historical approaches, with qualitative analysis based on systematic interpretation of relevant legal norms. The findings indicate that although agrarian reform is formally recognized as one of the objectives of TCUN utilization, the regulation lacks explicit normative safeguards to prioritize land redistribution amid persistent inequality. Broad administrative discretion in the transfer and allocation of land creates potential uncertainty in policy orientation. This study underscores the need for stronger normative integration between the abandoned land regime and agrarian reform policy to ensure that state land management advances social justice. Clear prioritization within TCUN utilization is essential to uphold the social function of land and the constitutional mandate of equitable distribution.